COMPARISON OF NEW TECHNIQUE OF APICAL SUPPORT USING MODIFIED UTEROSACRAL LIGAMENT FIXATION (MEUSL) VERSUS SACROSPINOUS LIGAMENT FIXATION (SSF) - Nusee, Zalina; MN, Nurul Hikmah (International Journal of Allied Health Sciences, 2021)
Background: Prevention of apical prolapse during vaginal hysterectomy is crucial in order to ensure good outcome of the surgery. The choice of the best method for apical support remains debatable. This study compared a new technique of apical support done during vaginal hysterectomy: Modified Extraperitoneal Uterosacral Ligament fixation (MEUSL) versus Sacrospinous Ligament fixation (SSF). Method: This is a retrospective study involving 48 patients with stage 3 and 4 uterovaginal prolapse, looking into the outcome of lower urinary tract symptoms, operative complications, symptom recurrence, and surgical failure. Results: Surgical failure at 6 months is significantly higher in the SSF group (p=0.043). There was no difference in terms of lower urinary tract symptoms. However, MEUSL had a significantly higher blood loss as compared to SSF group. Conclusion: MEUSL is an effective technique for the treatment of apical prolapse as it has lower risk of surgical failure with minimal complication. A future study regarding long term outcome between the two procedure is recommended to guide surgeons to choose the best treatment option.